2022
DOI: 10.3390/cimb44070202
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Silver Nanoparticles at Two Different Particle Sizes: Comparative Study with and without Silymarin

Abstract: Silver nanoparticles have been used for numerous therapeutic purposes because of their increased biodegradability and bioavailability, yet their toxicity remains questionable as they are known to interact easily with biological systems because of their small size. This study aimed to investigate and compare the effect of silver nanoparticles’ particle size in terms of their potential hazard, as well as their potential protective effect in an LPS-induced hepatotoxicity model. Liver slices were obtained from Spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…The technical information of AFM equipment are: AFM 5600LS, Agilent, Santa Clara, CA, USA. The sample preparation for AFM investigation was performed according to Elfaky et al 50 .…”
Section: Methodsmentioning
confidence: 99%
“…The technical information of AFM equipment are: AFM 5600LS, Agilent, Santa Clara, CA, USA. The sample preparation for AFM investigation was performed according to Elfaky et al 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Kunjiappan et al [50] reported that the gold nanoparticles biogenically synthesized by Azolla microphylla extract confirmed effective antioxidant and hepatoprotective effects. The large size of silver nanoparticles, compared to the small size of silver nanoparticles, displayed more hepatoprotective capabilities [51]. Cytocompatibility screening assays support a grade of cell death produced by bionanomaterial when exposed to normal cells; the results of cytotoxicity assay revealed that silver nanoparticles, even at higher concentrations, have nontoxic normal cells (human fibroblast (L929) cell lines); these results open new possibilities for their application in various biomedical fields [52].…”
Section: Evaluation Of In Vitro Hepatoprotective Activitymentioning
confidence: 99%
“…Figure 3 shows the results of UV-vis analysis of AgPg aq . According to several research [22][23][24][25][26], a surface plasmon resonance (SPR) peak with a wavelength between 400 and 490 nm suggests that the particle under investigation is in the nano range (below 100 nm).…”
Section: Uv-visible Spectrophotometermentioning
confidence: 99%
“…The synthesized nanoparticles must then be characterized for properties such as size, shape, and stability using a variety of techniques such as scanning electron microscopy (SEM), ultraviolet visible spectrophotometer (UV-Vis), Fourier transform infrared spectroscopy (FT-IR), dynamic light scattering analysis (DLS), and zeta potential analysis [23,24]. Many workers have reported that the silver nanoparticles synthesized using plant extracts have enhanced alleviating effect as compared to extract alone on various parameters of mammalian model in laboratory conditions [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%